Lithium-rich lithium iron oxide material and preparation method and application thereof

By setting a carbon layer and a mixed layer of polyethylene oxide and lithium salt outside the Li5FeO4 core, the problem of air sensitivity of the negative electrode material Li5FeO4 in lithium-ion batteries is solved, the stability and conductivity of the battery are improved, and the battery capacity and Battery life.

CN118198536BActive Publication Date: 2025-01-10HUBEI WANRUN NEW ENERGY TECH CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410460708.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-16
Publication Date
2025-01-10
Estimated Expiration
2044-04-16

AI Technical Summary

Technical Problem

The existing high-capacity negative electrode material in lithium-ion batteries has severe Li+ consumption due to the formation of SEI film, which affects the battery capacity. The positive electrode material Li5FeO4 is sensitive to water and CO2 in the air, has poor stability, and affects the industrialization process.

Method used

The lithium-rich lithium ferrate material adopts a core-shell structure, with a core of Li5FeO4, is coated with a carbon layer and a mixed layer including polyethylene oxide and lithium salt. The air stability is improved through double-layer coating and enhanced electrical conductivity.

Benefits of technology

It effectively improves the air stability and ionic conductivity of lithium-rich lithium ferrate materials, and improves the overall capacity and battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118198536B_ABST
    Figure CN118198536B_ABST
Patent Text Reader

Abstract

The present application provides a lithium-rich lithium iron oxide material and a preparation method and application thereof, which belongs to the field of positive electrode materials, wherein the lithium-rich lithium iron oxide material comprises a core-shell structure particle, wherein the core-shell structure particle comprises a core, a first coating layer coated outside the core, and a second coating layer coated outside the first coating layer; wherein the core is Li 5 FeO 4 , the first coating layer is a carbon layer, and the second coating layer is a mixed layer including polyethylene oxide and lithium salt; wherein the mass ratio of the first coating layer to the core is (2:100) to (10:100), and the mass ratio of the second coating layer to the core is (3:100) to (13:100). This application is conducive to improving the air stability of lithium ferrite materials, and at the same time, it can also increase the overall ionic conductivity of the electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery positive electrode materials, and in particular to a lithium-rich lithium ferrite material and a preparation method and application thereof. Background Art

[0002] With the rapid development of new energy, lithium-ion batteries have received extensive attention, and the endurance of electric vehicles has always been the key to restricting their further market entry. Existing high-capacity negative electrodes, such as hard carbon negative electrodes and silicon negative electrodes, have high capacity, but they will form a large amount of solid electrolyte interface film, namely SEI film, which causes the positive electrode to irreversibly consume a large amount of Li + , which seriously affects the overall capacity of lithium-ion batteries. The Li consumed by SEI film formation is compensated by pre-lithiation. + , is the most effective solution to solve the low initial efficiency of high-capacity negative electrodes.

[0003] In order to further promote the use of a new generation of high-capacity negative electrodes in future lithium-ion batteries, many pre-lithiation schemes have been developed to match the battery with a high-capacity, low-initial-efficiency negative electrode to compensate for the loss of active lithium during the initial cycle. Pre-lithiation strategies mainly include positive electrode pre-lithiation and negative electrode pre-lithiation. Among them, negative electrode pre-lithiation received extensive attention in the early days. In recent years, positive electrode pre-lithiation strategies have received more and more attention due to their advantages such as high safety, low price, easy synthesis, and high rechargeability.

[0004] Among the lithium supplements used in the positive electrode pre-lithiation, Li5FeO4 has a capacity of 864 mAh g -1 Theoretically, the specific capacity of Li5FeO4 is enough to greatly improve the capacity attenuation caused by the combination of existing positive electrode and new negative electrode such as hard carbon and silicon oxide. Li5FeO4 can match well with existing positive electrode materials and is compatible with existing binder systems. It can be directly added to positive electrode materials. In addition, Li5FeO4 is relatively cheap compared to other lithium supplements, so it has a good application prospect as a positive lithium-rich additive. However, it is very sensitive to water and CO2 in the air and has poor stability in the air, which seriously affects its industrialization process. Summary of the invention

[0005] In view of the technical problems existing in the background technology, the present application provides a lithium-rich lithium iron oxide material and a preparation method and application thereof, aiming to improve the stability of the lithium-rich lithium iron oxide material in the air.

[0006] In a first aspect, an embodiment of the present application provides a lithium-rich lithium iron oxide material, including core-shell structure particles, wherein the core-shell structure particles include an inner core, a first coating layer coated outside the inner core, and a second coating layer coated outside the first coating layer; wherein the inner core is Li5FeO4, the first coating layer is a carbon layer, and the second coating layer is a mixed layer including polyethylene oxide and a lithium salt; wherein the mass ratio of the first coating layer to the inner core is (2:100) to (10:100), and the mass ratio of the second coating layer to the inner core is (3:100) to (13:100).

[0007] In the present application, the lithium iron phosphate-rich material provided is provided with the first coating layer and the second coating layer in sequence outside the inner core containing Li5FeO4, wherein the first coating layer is a carbon layer, and the second coating layer is a mixed layer including polyethylene oxide (PEO) and a lithium salt. By sequentially arranging the first coating layer and the second coating layer outside the inner core, on the one hand, through the double-layer coating, the Li5FeO4 in the inner core can be prevented from being affected by moisture and carbon dioxide in the air, and the air stability of the lithium iron phosphate-rich material can be improved. On the other hand, the second coating layer as the outermost layer is a mixed layer including polyethylene oxide and a lithium salt, wherein polyethylene oxide can increase the conductivity of the material, improve the strength and uniformity of the coating layer, and the lithium salt can further improve the conductivity of the coating layer, thereby effectively increasing the ionic conductivity of the lithium iron phosphate-rich material.

[0008] In some embodiments, the mass ratio of the polyethylene oxide to the core is (0.5:100) to (5:100), and the mass ratio of the lithium salt to the core is (2:100) to (8:100).

[0009] In this embodiment, under the condition that the dosage of other components is the same, if the dosage of polyethylene oxide is too high, it will cause the particles of the lithium iron ore-rich material to stick to each other. If the dosage of polyethylene oxide is too low, complete and continuous coating cannot be achieved. If the dosage of lithium salt is too high, the polyethylene oxide content in the mixed layer will decrease, and the viscosity between the carbon layer and the mixed layer will decrease, and the strength of the mixed layer will also be reduced. If the dosage of lithium salt is too low, the conductivity of the lithium iron ore-rich material will be reduced.

[0010] In some embodiments, the mass ratio of the polyethylene oxide to the core is (0.5:100) to (2:100), and the mass ratio of the lithium salt to the core is (2:100) to (4:100).

[0011] In this embodiment, by adjusting the amount of polyethylene oxide and lithium salt in the second coating layer, when the mass ratio of the polyethylene oxide to the inner core is (0.5:100) to (2:100), and the mass ratio of the lithium salt to the inner core is (2:100) to (4:100), the conductive performance, coating uniformity and continuity can be taken into account, and the mutual adhesion between the lithium iron-rich material particles can be avoided as much as possible.

[0012] In some embodiments, the mass ratio of the carbon layer to the inner core is (5:100) to (7:100).

[0013] In this embodiment, by setting the mass ratio of the carbon layer to the inner core to (5:100) ~ (7:100), on the one hand, continuous and uniform coating of the inner core by the carbon layer can be achieved, and on the other hand, it is avoided that the proportion of the carbon layer is too high, which causes other properties of the prepared lithium-rich lithium iron phosphate material to be affected. Therefore, under the premise of maintaining uniform coating of the inner core, the prepared lithium-rich lithium iron phosphate material can have higher capacity and stability.

[0014] In some embodiments, the lithium salt is selected from at least one of lithium bis(fluorosulfonyl)imide, lithium hexafluorophosphate, and lithium fluoride.

[0015] In this embodiment, the conductivity of the mixed layer can be effectively improved by selecting at least one of lithium bis(fluorosulfonyl)imide, lithium hexafluorophosphate and lithium fluoride.

[0016] In some embodiments, the molecular weight of the polyethylene oxide is 50,000 to 150,000 Da.

[0017] In this embodiment, high molecular weight polyethylene oxide easily forms a uniform and continuous polymer network structure, providing better ion conductivity performance. However, if the molecular weight of polyethylene oxide is too high, it is difficult to achieve uniform coating on the surface of the carbon layer. Therefore, polyethylene oxide with a molecular weight of 50,000 to 150,000 Da is selected.

[0018] In some embodiments, the D90 particle size of the inner core is 3-5.5 μm.

[0019] In this embodiment, by controlling the particle size of the inner core, it is beneficial to control the particle size of the finally prepared lithium-rich lithium iron oxide material within a smaller range. The lithium-rich lithium iron oxide material with a small particle size is beneficial for uniform mixing with other components in the positive electrode active material, which in turn is beneficial for the relatively uniform distribution of the lithium-rich lithium iron oxide material on the current collector.

[0020] In some embodiments, the average thickness of the first coating layer is 5-10 nm, and the average thickness of the second coating layer is 5-10 nm.

[0021] In this embodiment, uniform and continuous coating is achieved while reducing the thickness of the coating layer, which is beneficial to ensuring the capacity of the lithium-rich lithium iron oxide material, improving the conductivity, and maintaining the lithium-rich lithium iron oxide material with a smaller particle size.

[0022] In a second aspect, the present application provides a method for preparing the aforementioned lithium-rich lithium iron oxide material, comprising:

[0023] Providing a core and a coating liquid;

[0024] forming a first coating layer on the surface of the core to obtain an intermediate product;

[0025] Mixing the intermediate product with a coating liquid to form a second coating layer on the surface of the first coating layer to obtain the lithium-rich lithium ferrite material;

[0026] Wherein, the coating solution includes a solvent, polyethylene oxide and a lithium salt.

[0027] In this embodiment, the lithium-rich lithium iron oxide material can be obtained by coating the Li5FeO4-containing core in two steps. The preparation method is relatively simple, and a lithium-rich lithium iron oxide material with a small particle size of 3 to 5.5 μm can be obtained. The prepared lithium-rich lithium iron oxide material has good air stability and ion conductivity.

[0028] In some embodiments, the step of forming the first coating layer on the surface of the inner core includes: mixing the inner core with a carbon source and a grinding aid and ball milling the mixture, and then carbonizing the mixture to obtain the intermediate product.

[0029] In this embodiment, the ball milling method is beneficial to more uniform mixing of the inner core and the carbon source, wherein the grinding aid needs to be removed before the carbonization treatment. Through the carbonization treatment step, a first coating layer (carbon layer) can be formed on the surface of the inner core, that is, an intermediate product is obtained.

[0030] In some embodiments, the carbon source is selected from at least one of polypropylene, glucose and high-temperature coal tar.

[0031] In this embodiment, polypropylene, glucose and high-temperature coal tar are all widely available and inexpensive, which is conducive to reducing costs. Among them, high-temperature coal tar, in particular, has high stability and is more effective as a carbon source in improving the stability of lithium iron-rich lithium materials.

[0032] In some embodiments, the carbonization treatment is carried out at a temperature of 500-700° C. and for a time of 1.5-3 h.

[0033] In this embodiment, if the carbonization temperature is too low, carbonization cannot be fully achieved, and if the carbonization temperature is too high, the structure of Li5FeO4 in the inner core will be affected. Therefore, in this embodiment, the carbonization temperature is selected to be 500~700℃ and the time is 1.5~3h to ensure that a uniformly coated carbon layer can be formed without affecting the structure of the inner core.

[0034] In some embodiments, before forming the first coating layer on the surface of the core to obtain the intermediate product, the process further includes preparing the core, and the preparation method includes:

[0035] The mixture of the iron source and the lithium source is placed in an inert atmosphere and calcined at 500-700° C. for 24-48 hours.

[0036] In this embodiment, the mixture of the iron source and the lithium source is placed in an inert atmosphere and calcined at 500-700°C for 24-48 hours, which is conducive to the complete reaction of the iron source and the lithium source. If the calcination temperature is too low or the time is too short, the product crystallinity is poor, and if the sintering temperature is too high or the time is too long, it will cause structural damage, which will affect the lithium replenishment effect of the prepared lithium-rich lithium iron oxide material.

[0037] In some embodiments, the iron source is Fe2O3.

[0038] In this embodiment, compared with other iron sources such as iron hydroxide, the use of Fe2O3 is more conducive to obtaining a Li5FeO4 core with a small particle size.

[0039] In some embodiments, the iron source has a D90 particle size less than or equal to 400 nm.

[0040] In this embodiment, the particle size of the iron source will affect the particle size of the core, and further affect the particle size of the final prepared lithium-rich lithium iron oxide material. If the particle size of the iron source is too large, the particle size of the final prepared lithium-rich lithium iron oxide material will also be large, which is not conducive to its uniform distribution on the current collector. Preferably, the D90 particle size of the iron source is 200~400nm. When the D90 particle size of the iron source is 200~400nm, it is conducive to obtaining a small-particle-size Li5FeO4 core.

[0041] In some embodiments, the lithium source is selected from at least one of lithium oxide, lithium hydroxide and lithium carbonate.

[0042] In this embodiment, the sources of lithium oxide, lithium hydroxide and lithium carbonate are extensive, which is conducive to mass production and improves the industrial practicability of the method.

[0043] In some embodiments, the lithium source is a mixture of lithium oxide and lithium hydroxide.

[0044] In this embodiment, considering that the decomposition temperature of lithium carbonate is too high and it is highly corrosive to the container, lithium hydroxide alone as a lithium source will cause serious agglomeration, and the cost of lithium oxide is relatively high, therefore, a mixture of lithium hydroxide and lithium oxide is selected as the lithium source to reduce costs and avoid agglomeration.

[0045] In some embodiments, the lithium source is a mixture of lithium oxide and lithium hydroxide in a molar ratio of (1.5-2.5):1.

[0046] In this embodiment, by setting the lithium source as a mixture of lithium oxide and lithium hydroxide in a molar ratio of (1.5-2.5):1, on the one hand, agglomeration can be avoided, and on the other hand, it is conducive to reducing costs.

[0047] In some embodiments, the molar ratio of Fe to Li in the mixture is (1:5.0) to (1:5.2).

[0048] In this embodiment, introducing a slightly excessive amount of lithium is beneficial to increasing the lithium content in the lithium supplement agent, thereby improving the lithium supplement effect.

[0049] In some embodiments, the intermediate product is mixed with a coating liquid, the solvent is removed, and the mixture is ground and sieved to form a second coating layer on the surface of the first coating layer to obtain the lithium-rich lithium ferrite material.

[0050] In this embodiment, the solvent can be acetonitrile or a solvent with a polarity similar to acetonitrile. The presence of the solvent is conducive to the uniform and continuous coating of polyethylene oxide and the lithium source on the surface of the intermediate product. However, it should be noted that, considering only the properties of polyethylene oxide itself, although high molecular weight polyethylene oxide is easy to form a uniform and continuous polymer network structure, the high molecular weight of polyethylene oxide will make it more difficult to dissolve in solvents such as acetonitrile, which will affect the continuity and uniformity of the coating.

[0051] In a third aspect, an embodiment of the present application provides a positive electrode plate, comprising a current collector and an active material layer arranged on at least one side of the current collector, wherein the active material layer comprises the lithium-rich lithium iron oxide material described in any one of the preceding items or the lithium-rich lithium iron oxide material obtained by any one of the preparation methods described in the preceding items.

[0052] In this embodiment, the active material layer of the positive electrode plate includes lithium-rich lithium iron oxide material. Since the stability of the lithium-rich lithium iron oxide material in the air is significantly improved, it is beneficial to the lithium replenishment effect, so that the positive electrode plate containing it can be used in the battery to ensure the overall capacity of the battery.

[0053] In some embodiments, the mass fraction of the lithium-rich lithium ferrite material in the active material layer is (2-8) wt %, which makes up for the Li consumed in the formation of the SEI film. + .

[0054] In a fourth aspect, an embodiment of the present application provides a secondary battery, comprising the aforementioned positive electrode plate.

[0055] In this embodiment, the secondary battery includes the above-mentioned positive electrode plate, thereby maintaining a relatively high capacity.

[0056] In a fifth aspect, an embodiment of the present application provides an electrical device, comprising the aforementioned secondary battery.

[0057] In this embodiment, the electric device includes the secondary battery, and thus has the advantage of a long battery life.

[0058] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0060] Figure 1 This is a schematic diagram of the structure of the lithium-rich lithium iron oxide material in the embodiment of the present application;

[0061] Figure 2 This is a schematic diagram of a process for preparing a lithium-rich lithium iron oxide material in an embodiment of the present application;

[0062] Figure 3 Schematic diagram of the process for preparing the lithium-rich lithium iron oxide material in Example 1 of the present application;

[0063] Figure 4 This is a SEM test image of the lithium-rich lithium iron oxide material prepared in Example 1 of the present application;

[0064] Figure 5 This is a SEM test image of the lithium-rich lithium iron oxide material prepared in Example 1 of the present application;

[0065] Figure 6 The specific capacity data of the lithium-rich lithium iron oxide materials prepared in Examples 1 to 3 of the present application;

[0066] Figure 7 This is the XRD test diagram of Li5FeO4 before and after coating in Example 1 of the present application. DETAILED DESCRIPTION

[0067] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0068] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0069] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0070] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0071] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0072] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).

[0073] In the description of the embodiments of the present application, the technical terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, which are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the embodiments of the present application.

[0074] Li5FeO4 has a good application prospect because of its high theoretical specific capacity, good matching with existing positive electrode materials, good compatibility with existing adhesives and relatively low price. However, it is very sensitive to water and CO2 in the air, and has poor stability in the air, which seriously affects its industrialization process. In order to solve the technical problem of poor stability of lithium-rich ferrite materials in the air, the present application provides a lithium-rich ferrite material and a preparation method thereof, a positive electrode sheet, a secondary battery and an electrical device, wherein a carbon layer and a mixed layer composed of polyethylene oxide and a lithium salt are arranged outside the inner core containing Li5FeO4, so as to achieve the technical effect of improving the stability of the lithium-rich ferrite material in the air, and then the electrical performance of the positive electrode sheet, the secondary battery and the electrical device is also improved.

[0075] The electric device provided in the embodiment of the present application may be, but is not limited to, a mobile phone, a tablet, a laptop computer, an electric toy, an electric tool, a battery car, an electric car, a ship, a spacecraft, etc. Among them, the electric toy may include a fixed or mobile electric toy, such as a game console, an electric car toy, an electric ship toy, and an electric airplane toy, etc., and the spacecraft may include an airplane, a rocket, a space shuttle, and a spacecraft, etc.

[0076] Please refer to Figure 1 In the first aspect, the embodiment of the present application provides a lithium-rich lithium iron oxide material, including core-shell structure particles, the core-shell structure particles including an inner core, a first coating layer coated outside the inner core, and a second coating layer coated outside the first coating layer; wherein the inner core is Li5FeO4, the first coating layer is a carbon layer, and the second coating layer is a mixed layer including polyethylene oxide and a lithium salt; wherein the mass ratio of the first coating layer to the inner core is (2:100) to (10:100), and the mass ratio of the second coating layer to the inner core is (3:100) to (13:100).

[0077] The lithium iron phosphate rich material of the present application is provided with a first coating layer and a second coating layer in sequence outside the inner core containing Li5FeO4, wherein the first coating layer is a carbon layer, and the second coating layer is a mixed layer including polyethylene oxide and a lithium salt. By arranging the first coating layer and the second coating layer in sequence outside the inner core, on the one hand, through the double-layer coating, the Li5FeO4 in the inner core can be prevented from being affected by moisture and carbon dioxide in the air, thereby improving the air stability of the lithium iron phosphate rich material; on the other hand, the second coating layer as the outermost layer is a mixed layer including polyethylene oxide and a lithium salt, i.e., a solid electrolyte layer, which can increase the overall electronic conductivity and ionic conductivity of the lithium iron phosphate rich material.

[0078] Among them, the mass ratio of the first coating layer to the core is (2:100)~(10:100), and the mass ratio of the second coating layer to the core is (3:100)~(13:100). For the first coating layer, due to the low specific capacity of the carbon layer, if the proportion of the carbon layer is too large, the overall capacity of the prepared lithium-rich lithium iron oxide material will be reduced. If the proportion of the carbon layer is too small, complete and continuous coating cannot be achieved, and the core containing Li5FeO4 cannot be effectively isolated from the air. For the second coating layer, if the proportion of the mixed layer is too large, the particles of the prepared lithium-rich lithium iron oxide material will be bonded to each other, thereby increasing the particle size of the lithium-rich lithium iron oxide material. If the proportion of the mixed layer is too small, complete and continuous coating cannot be achieved, and the core containing Li5FeO4 cannot be effectively isolated from the air. At the same time, it will also affect the overall electronic conductivity and ionic conductivity of the lithium-rich lithium iron oxide material. Therefore, a second coating layer proportion that is as small as possible and can form a complete and continuous coating layer is selected.

[0079] Specifically, the mass ratio of the first coating layer to the core can be 2:100, 4:100, 6:100, 8:100, 10:100 or any value between (2:100) and (10:100); preferably, the mass ratio of the first coating layer to the core is (5:100) to (7:100); the mass ratio of the second coating layer to the core can be 3:100, 5:100, 7:100, 9:100, 11:100, 13:100 or any value between (3:100) and (13:100).

[0080] In some embodiments, the mass ratio of polyethylene oxide to the core is (0.5:100) to (5:100), and the mass ratio of the lithium salt to the core is (2:100) to (8:100); preferably, the mass ratio of polyethylene oxide to the core is (0.5:100) to (2:100), and the mass ratio of the lithium salt to the core is (2:100) to (4:100).

[0081] Among them, polyethylene oxide, as a solid electrolyte, increases the conductivity of the material on the one hand, and has a certain degree of adhesion on the other hand, which can improve the strength and uniformity of the coating layer; lithium salt can further improve the conductivity of the coating layer. Among them, under the condition that the dosage of other components is the same, if the dosage of polyethylene oxide is too high, it will cause the particles of the lithium iron-rich material to stick to each other, and if the dosage of polyethylene oxide is too low, complete and continuous coating cannot be achieved; if the dosage of lithium salt is too high, the content of polyethylene oxide in the mixed layer is too low, the viscosity between the carbon layer and the mixed layer is reduced, and the strength of the mixed layer is reduced at the same time. If the dosage of lithium salt is too low, the conductivity of the lithium iron-rich material will be reduced.

[0082] Specifically, the mass ratio of polyethylene oxide to the inner core can be 0.5:100, 1:100, 2:100, 1.4:100, 3:100, 4:100, 5:100 or any value between (0.5:100) and (5:100); the mass ratio of lithium salt to the inner core can be 2:100, 3:100, 4:100, 5:100, 6:100, 7:100, 8:100 or any value between (2:100) and (8:100).

[0083] In some embodiments, the lithium salt is selected from at least one of lithium bis(fluorosulfonyl)imide, lithium hexafluorophosphate and lithium fluoride, specifically, it can be one of lithium bis(fluorosulfonyl)imide, lithium hexafluorophosphate and lithium fluoride, it can also be a mixture of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate, a mixture of lithium hexafluorophosphate and lithium fluoride, or a mixture of lithium bis(fluorosulfonyl)imide, lithium hexafluorophosphate and lithium fluoride.

[0084] In some embodiments, the molecular weight of polyethylene oxide is 50,000 to 150,000 Da, specifically 50,000 Da, 70,000 Da, 90,000 Da, 110,000 Da, 130,000 Da, 150,000 Da or any value between 50,000 and 150,000 Da, which is conducive to forming a uniform and continuous polymer network structure and providing better ion conduction performance.

[0085] In some embodiments, the D90 particle size of the inner core is 3-5.5 μm, specifically 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm or any value between 3-5.5 μm.

[0086] In some embodiments, the average thickness of the first coating layer is 5-10 nm, specifically 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm or any value between 5-10 nm.

[0087] In some embodiments, the average thickness of the second coating layer is 5-10 nm, specifically 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm or any value between 5-10 nm.

[0088] In a second aspect, the present application provides a method for preparing any of the aforementioned lithium-rich lithium iron oxide materials, such as Figure 2 As shown, including:

[0089] S1, providing a core and a coating liquid;

[0090] S2, forming a first coating layer on the surface of the inner core to obtain an intermediate product;

[0091] S3, mixing the intermediate product with the coating liquid to form a second coating layer on the surface of the first coating layer to obtain a lithium-rich lithium ferrite material;

[0092] The coating solution includes a solvent, polyethylene oxide and a lithium salt.

[0093] The preparation method of the present application only requires two-step coating of the Li5FeO4-containing core to obtain a lithium-rich lithium ferrite material. The preparation method is relatively simple and can obtain a lithium-rich lithium ferrite material with a small particle size of 3~5.5μm in D90 particle size.

[0094] Specifically, in step S1, the method for preparing the inner core includes:

[0095] The mixture of the iron source and the lithium source is placed under an inert atmosphere and calcined at 500-700°C for 24-48 hours, wherein the calcination temperature can be 500°C, 550°C, 600°C, 650°C, 700°C or any value between 500-700°C, and the calcination time can be 24h, 28h, 32h, 36h, 40h, 44h, 48h or any value between 24-48h.

[0096] In some embodiments, a mixer may be used to uniformly mix the iron source and the lithium source. The mixing time may be adjusted according to the capacity and rotation speed of the mixer to ensure uniform mixing of the iron source and the lithium source as much as possible.

[0097] In some embodiments, during the calcination step, the mixture of the iron source and the lithium source may be fed into a sintering furnace for calcination, and an inert gas may be introduced in advance, wherein the amount of the inert gas introduced is 5 to 10 m 3 / h, so that the oxygen content in the sintering furnace is less than 1ppm, and the humidity is less than 5% to avoid the reaction of carbon dioxide and water with the mixture of the iron source and the lithium source. Thereafter, the sintering furnace is heated up for calcination at a heating rate of 3-7°C / min.

[0098] In some embodiments, the iron source is Fe2O3, and the D90 particle size of the iron source is less than or equal to 400 nm, specifically, it can be 400 nm, 350 nm, 300 nm, 250 nm, 200 nm, 150 nm, or any value less than or equal to 400 nm. Preferably, the D90 particle size of the iron source is 200-400 nm.

[0099] In some embodiments, the lithium source is selected from at least one of lithium oxide, lithium hydroxide and lithium carbonate. Preferably, the lithium source is a mixture of lithium oxide and lithium hydroxide. Specifically, the lithium source is a mixture of lithium oxide and lithium hydroxide in a molar ratio of (1.5-2.5):1, for example, the molar ratio of lithium oxide to lithium hydroxide can be 1.5:1, 1.7:1, 1.9:1, 2.1:1, 2.3:1, 2.5:1 or any value between (1.5-2.5):1.

[0100] In some embodiments, the molar ratio of Fe to Li in the mixture of the iron source and the lithium source is 1:(5.0-5.2), specifically 1:5.0, 1:5.05, 1:5.1, 1:5.15, 1:5.2 or any value between 1:(5.0-5.2).

[0101] It should be noted that the Li5FeO4 obtained in this embodiment needs to be crushed before use. Specifically, it can be crushed by air flow crushing. For example, the sintered Li5FeO4 is crushed by air flow crushing, keeping the dew point below -30°C, to obtain pure phase Li5FeO4 with a particle size range of 3~5.5μm.

[0102] Specifically, in step S2, the step of forming the first coating layer on the surface of the inner core includes: mixing the inner core with a carbon source and a grinding aid and ball milling the mixture, and then carbonizing the mixture to obtain an intermediate product.

[0103] In this embodiment, ball milling is used to evenly mix the core and the carbon source. The rotation speed during ball milling can be set to 300-600 rpm, the time is 1-5 hours, and the ball-to-material ratio is (8-12):1. The grinding aid needs to be removed before carbonization. The grinding aid is an alcohol compound, such as ethanol, etc. The grinding aid can be removed by drying to volatilize the grinding aid.

[0104] In some embodiments, the carbon source is selected from at least one of polypropylene, glucose and high temperature coal tar. For example, the carbon source can be polypropylene, glucose, high temperature coal tar, a mixture of polypropylene and glucose, a mixture of glucose and high temperature coal tar, and a mixture of polypropylene, glucose and high temperature coal tar.

[0105] It should be noted that coal tar is a multiphase system. Its basic components are aliphatic hydrocarbons, cycloalkanes, polycyclic hydrocarbons, condensed ring hydrocarbons and heterocyclic aromatic hydrocarbons. It is in a glassy phase at room temperature and softens and then melts when heated. Therefore, it is classified into low-temperature coal tar (CTPD) ≤75°C, medium-temperature coal tar (CTPZ) 75.95°C and high-temperature coal tar (CTPG) ≥95°C according to its softening point.

[0106] In some embodiments, the carbonization treatment temperature is 500-700°C, specifically 500°C, 550°C, 600°C, 650°C, 700°C or any value between 500-700°C, and the time is 1.5-3h, specifically 1.5, 2, 2.5, 3h or any value between 1.5-3h.

[0107] In the present application, the carbonization step is to place the carbon source coated Li5FeO4 precursor in a sintering furnace for high temperature calcination. In order to reduce the oxidation of the carbon source, an inert gas needs to be introduced in advance. The amount of inert gas introduced can be 3-7 m 3 / h, so that the oxygen content in the sintering furnace is less than 1 ppm and the humidity is less than 5% to prevent oxygen and water from reacting with the carbon source and affecting the carbonization process; thereafter, the sintering furnace is heated to 500~700°C at a heating rate of 3~7°C / min and kept warm for 1.5~3h to obtain an intermediate product, and the intermediate product is air flow crushed to maintain the dew point below ~30°C to obtain an intermediate product with a particle size of 3~5.5μm.

[0108] Specifically, in step S3, the lithium iron oxide-rich lithium material is obtained by mixing the intermediate product with the coating liquid, removing the solvent, grinding and sieving, wherein the solvent can be selected from acetonitrile or a solvent with a polarity similar to acetonitrile, and the amount of solvent used needs to allow the polyethylene oxide to be completely dissolved. If the solvent is too much, it can be removed by drying later, which has little effect on the overall performance of the material, but will prolong the time for solvent removal and increase energy consumption, affecting production efficiency and cost. If the solvent is too little, the polyethylene oxide cannot be completely dissolved, which will affect the uniformity and continuity of the coating layer.

[0109] Furthermore, in the coating liquid, the mass ratio of polyethylene oxide to lithium salt is 20%-50%, specifically 20%, 30%, 40%, 50% or any value between 20% and 50%, preferably 30%-40%. By adjusting the ratio of polyethylene oxide to lithium salt, when the mass ratio of polyethylene oxide to the inner core is (0.5:100)~(2:100), the mass ratio of lithium salt to the inner core is (2:100)~(4:100), and the mass ratio of polyethylene oxide to lithium salt is 20%-50%, it is possible to further take into account the conductive properties, uniformity and continuity of the coating, and avoid mutual adhesion between the lithium ferrite-rich lithium material particles.

[0110] Furthermore, the removal speed can be increased by increasing the temperature during the solvent removal process, but the temperature should not be too high to avoid damaging the structure of the lithium iron oxide rich material. In addition, the lithium iron oxide rich material can be crushed after the solvent is removed, and the crushing method can specifically adopt air flow crushing to reduce the particle size.

[0111] In a third aspect, an embodiment of the present application provides a positive electrode plate, comprising a positive electrode current collector and an active material layer arranged on at least one side of the positive electrode current collector, wherein the active material layer comprises any of the aforementioned lithium iron ore-rich materials or a lithium iron ore-rich material prepared by any of the aforementioned preparation methods.

[0112] In some embodiments, the mass fraction of the lithium ferrite-rich material in the active material layer is (2~8) wt%, specifically 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt% or any value between (2~8) wt%, and the specific amount can be determined according to the lithium replenishment efficiency.

[0113] In a fifth aspect, an embodiment of the present application provides an electrical device, such as a vehicle, comprising a secondary battery as described in the above embodiment.

[0114] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.

[0115] 1. Preparation method

[0116] Example 1

[0117] This embodiment provides a method for preparing a lithium-rich lithium iron oxide material, comprising the following steps:

[0118] (1) Weigh nano-Fe2O3 with a D90 of 300 nm, Li2O and LiOH, keep Fe:Li=1:5.1, and LiOH:Li2O in the lithium source=1:2, place them in a mixer, and stir for 30 minutes until they are evenly mixed to obtain a mixed raw material;

[0119] (2) The mixed raw materials are sent into a sintering furnace for calcination, and high-purity nitrogen is introduced in advance at a rate of 5m 3 / h, make the oxygen content less than 1ppm and the humidity less than 5%, then raise the sintering furnace to 600°C at a heating rate of 5°C / min and keep it at that temperature for 36h to obtain pure phase Li5FeO4;

[0120] (3) Grinding the sintered Li5FeO4 by air flow to keep the dew point below -30°C to obtain pure phase Li5FeO4 with small particle size;

[0121] (4) Weigh 200 g of crushed Li5FeO4, 20 g of high-temperature coal tar pitch and an appropriate amount of anhydrous ethanol, mix them evenly, place them in a ball mill, and mill them at 450 rpm for 3 h at a ball-to-material ratio of 10:1 to coat the asphalt on the Li5FeO4 to obtain an asphalt-coated Li5FeO4 precursor;

[0122] (5) The asphalt-coated Li5FeO4 precursor was placed in a sintering furnace for high-temperature calcination, and high-purity nitrogen was introduced in advance at a flow rate of 5 m 3 / h, to make the oxygen content less than 1ppm and the humidity less than 5%, then raise the sintering furnace to 550°C at a heating rate of 5°C / min, keep it at that temperature for 2h, and air flow pulverize the product to keep the dew point below ~30°C to obtain Li5FeO4@C, in which the mass ratio of carbon layer to core is 6:100;

[0123] (6) Polyethylene oxide (molecular weight of 100,000 Da) and LIFSI (polyethylene oxide monomer: LIFSI = 40%) were placed in anhydrous acetonitrile and stirred for 3 h to completely dissolve them. Li5FeO4@C was placed therein (the mass ratio of polyethylene oxide to Li5FeO4 was 1%) and stirred and evaporated until the acetonitrile was completely evaporated. The product was subjected to air flow pulverization to obtain a lithium iron-rich lithium material (wherein the mass ratio of polyethylene oxide to Li5FeO4 was 1:100, the mass ratio of LIFSI to Li5FeO4 was 2.5:100, and the mass ratio of the second coating layer to Li5FeO4 was 3.5:100). SEM and XRD results were as follows: Figure 4 , Figure 5 and Figure 7 shown.

[0124] Example 2

[0125] This embodiment provides a method for preparing a lithium-rich lithium ferrite material, which is different from Embodiment 1 only in that the carbon layer content is reduced to a mass ratio of the carbon layer to the core of 2:100.

[0126] Example 3

[0127] This embodiment provides a method for preparing a lithium-rich lithium ferrite material, which is different from Embodiment 1 only in that the carbon layer content is increased to a mass ratio of the carbon layer to the core of 8:100.

[0128] Example 4

[0129] This embodiment provides a method for preparing a lithium-rich lithium ferrite material, which is different from Embodiment 1 only in that the carbon layer content is increased to a mass ratio of the carbon layer to the core of 10:100.

[0130] Example 5

[0131] This embodiment provides a method for preparing a lithium-rich lithium iron oxide material, comprising the following steps:

[0132] (1) Weigh nano-Fe2O3 with a D90 of 300 nm, Li2O and LiOH, keep Fe:Li=1:5.1, and LiOH:Li2O in the lithium source=1:2, place them in a mixer, and stir for 30 minutes until they are evenly mixed to obtain a mixed raw material;

[0133] (2) The mixed raw materials are sent into a sintering furnace for calcination, and high-purity nitrogen is introduced in advance at a rate of 5m 3 / h, make the oxygen content less than 1ppm and the humidity less than 5%, then raise the sintering furnace to 600°C at a heating rate of 5°C / min and keep it at that temperature for 36h to obtain pure phase Li5FeO4;

[0134] (3) Grinding the sintered Li5FeO4 by air flow to keep the dew point below -30°C to obtain pure phase Li5FeO4 with small particle size;

[0135] (4) Weigh 200 g of the crushed Li5FeO4, 20 g of polypropylene and an appropriate amount of anhydrous ethanol, mix them evenly, place them in a ball mill, and mill them at 450 rpm for 3 h at a ball-to-material ratio of 10:1 to coat the Li5FeO4 with polypropylene to obtain a polypropylene-coated Li5FeO4 precursor;

[0136] (5) The polypropylene-coated Li5FeO4 precursor was placed in a sintering furnace for high-temperature calcination, and high-purity nitrogen was introduced in advance at a flow rate of 5 m 3 / h, to make the oxygen content less than 1ppm and the humidity less than 5%, then raise the sintering furnace to 400°C at a heating rate of 5°C / min, keep it warm for 2h, and air flow pulverize the product to keep the dew point below ~30°C to obtain Li5FeO4@C, in which the mass ratio of carbon layer to core is 6:100;

[0137] (6) Polyethylene oxide (molecular weight of 10 Da) and LIFSI (polyethylene oxide monomer: LIFSI = 40%) were placed in anhydrous acetonitrile and stirred for 3 h to completely dissolve them, Li5FeO4@C was placed therein, stirred and evaporated until the acetonitrile was completely evaporated, and the product was subjected to air flow pulverization to obtain a lithium iron-rich lithium material (wherein the mass ratio of polyethylene oxide to Li5FeO4 was 1:100, the mass ratio of LIFSI to Li5FeO4 was 2.5:100, and the mass ratio of the second coating layer to Li5FeO4 was 3.5:100).

[0138] Example 6

[0139] This embodiment provides a method for preparing a lithium-rich lithium ferrite material, which is different from Embodiment 5 only in that the carbon layer content is reduced to a mass ratio of the carbon layer to the core of 2:100.

[0140] Example 7

[0141] This embodiment provides a method for preparing a lithium-rich lithium ferrite material, which is different from Embodiment 5 only in that the carbon layer content is increased to a mass ratio of the carbon layer to the core of 8:100.

[0142] Example 8

[0143] This embodiment provides a method for preparing a lithium-rich lithium ferrite material, which is different from Embodiment 5 only in that the carbon layer content is increased to a mass ratio of the carbon layer to the core of 10:100.

[0144] Example 9

[0145] This embodiment provides a method for preparing a lithium-rich lithium iron oxide material, comprising the following steps:

[0146] (1) Weigh nano-Fe2O3 with a D90 of 300 nm, Li2O and LiOH, keep Fe:Li=1:5.1, and LiOH:Li2O in the lithium source=1:2, place them in a mixer, and stir for 30 minutes until they are evenly mixed to obtain a mixed raw material;

[0147] (2) The mixed raw materials are sent into a sintering furnace for calcination, and high-purity nitrogen is introduced in advance at a rate of 5m 3 / h, make the oxygen content less than 1ppm and the humidity less than 5%, then raise the sintering furnace to 600°C at a heating rate of 5°C / min and keep it at that temperature for 36h to obtain pure phase Li5FeO4;

[0148] (3) Grinding the sintered Li5FeO4 by air flow to keep the dew point below -30°C to obtain pure phase Li5FeO4 with small particle size;

[0149] (4) Weigh 200 g of the crushed Li5FeO4, 60 g of glucose and an appropriate amount of anhydrous ethanol, mix them evenly, place them in a ball mill, and mill them at 450 rpm for 3 h at a ball-to-material ratio of 10:1 to coat the glucose on the Li5FeO4 to obtain a glucose-coated Li5FeO4 precursor;

[0150] (5) The glucose-coated Li5FeO4 precursor was placed in a sintering furnace for high-temperature calcination, and high-purity nitrogen was introduced in advance at a flow rate of 5 m 3 / h, to make the oxygen content less than 1ppm and the humidity less than 5%, then raise the sintering furnace to 400°C at a heating rate of 5°C / min, keep it warm for 2h, and air flow pulverize the product to keep the dew point below ~30°C to obtain Li5FeO4@C, in which the mass ratio of carbon layer to core is 6:100;

[0151] (6) Place an appropriate amount of polyethylene oxide (molecular weight of 100,000 Da) and LIFSI (polyethylene oxide monomer: LIFSI = 40%) in anhydrous acetonitrile and stir for 3 h to completely dissolve them. Place Li5FeO4@C in it and stir and evaporate until the acetonitrile is completely evaporated. The product is subjected to air flow pulverization to obtain a lithium iron-rich lithium material (the mass ratio of polyethylene oxide to Li5FeO4 is 1%, the mass ratio of LIFSI to Li5FeO4 is 2.5:100, and the mass ratio of the second coating layer to Li5FeO4 is 3.5:100).

[0152] Example 10

[0153] This embodiment provides a method for preparing a lithium-rich lithium ferrite material, which differs from Embodiment 9 only in that the carbon layer content is reduced to a mass ratio of the carbon layer to the core of 2:100.

[0154] Embodiment 11

[0155] This embodiment provides a method for preparing a lithium-rich lithium ferrite material, which is different from Example 9 only in that the carbon layer content is increased to a mass ratio of the carbon layer to the core of 8:100.

[0156] Example 12

[0157] This embodiment provides a method for preparing a lithium-rich lithium ferrite material, which is different from Embodiment 9 only in that the carbon layer content is increased to a mass ratio of the carbon layer to the core of 10:100.

[0158] Example 13

[0159] This embodiment provides a method for preparing a lithium iron-rich lithium ferrate material, which is different from Example 1 only in that the mass ratio of polyethylene oxide to Li5FeO4 is 0.5:100, the mass ratio of LIFSI to Li5FeO4 is 2.5:100, and the mass ratio of the second coating layer to Li5FeO4 is 3:100.

[0160] Embodiment 14

[0161] This embodiment provides a method for preparing a lithium iron-rich lithium ferrate material, which is different from Example 1 only in that the mass ratio of polyethylene oxide to Li5FeO4 is 1:100, the mass ratio of LIFSI to Li5FeO4 is 2:100, and the mass ratio of the second coating layer to Li5FeO4 is 3:100.

[0162] Embodiment 15

[0163] This embodiment provides a method for preparing a lithium iron-rich lithium ferrate material, which is different from Example 1 only in that the mass ratio of polyethylene oxide to Li5FeO4 is 2:100, the mass ratio of LIFSI to Li5FeO4 is 6:100, and the mass ratio of the second coating layer to Li5FeO4 is 8:100.

[0164] Example 16

[0165] This embodiment provides a method for preparing a lithium iron-rich lithium ferrate material, which is different from Example 1 only in that the mass ratio of polyethylene oxide to Li5FeO4 is 5:100, the mass ratio of LIFSI to Li5FeO4 is 8:100, and the mass ratio of the second coating layer to Li5FeO4 is 13:100.

[0166] Comparative Example 1

[0167] This comparative example provides a method for preparing a lithium-rich lithium iron oxide material, which differs from Example 1 only in that step (6) is not included.

[0168] Comparative Example 2

[0169] This comparative example provides a method for preparing a lithium-rich lithium ferrite material, which differs from Example 1 only in that steps (4) and (5) are not included.

[0170] Comparative Example 3

[0171] This comparative example provides a method for preparing a lithium-rich lithium ferrite material, which differs from Example 1 only in that Fe2O3 in step 1 is replaced by ferric hydroxide.

[0172] Comparative Example 4

[0173] This comparative example provides a method for preparing a lithium-rich lithium ferrite material, which is different from Example 1 only in that the polyethylene oxide in step 1 is replaced by lithium aluminum titanium phosphate.

[0174] 2. Test Method

[0175] Particle size test: The particle size of the lithium-rich lithium ferrite material prepared in the embodiment and the comparative example was tested using a laser particle size analyzer. The results are shown in Table 1.

[0176] Capacity test:

[0177] The electrochemical performance test was conducted using a button-type semi-battery: the lithium-rich lithium iron oxide material obtained in the examples and comparative examples or the pure phase Li5FeO4 obtained in Example 2 was used as the positive electrode material, and the above positive electrode material, conductive carbon black, and binder PVDF (polyvinylidene fluoride) were mixed into a slurry at a ratio of 8:1:1, and evenly coated on aluminum foil to form a positive electrode sheet (electrode mixing, coating and other preparation processes were all completed in the air), a metal lithium sheet was used as the negative electrode sheet, 1 mol / L LiPF6 was used as the electrolyte, and the solvent was EC:DMC:EMC=1:1:1 (volume ratio), and the battery shell, positive and negative electrode sheets, diaphragm (PE double-layer ceramic diaphragm), spring sheet, and gasket were assembled into a button battery in a vacuum glove box. The electrochemical performance test was conducted, and the capacity test was conducted under 3.3~4.3V. The results are shown in Table 1 and Figure 6 .

[0178] Table 1

[0179] D90 (μm) Capacity (mAh / g) Example 1 4.8 728 Example 2 4.9 455 Example 3 5.1 526 Example 4 4.8 487 Example 5 5.0 634 Example 6 4.7 421 Example 7 4.9 509 Example 8 4.8 472 Example 9 4.6 622 Example 10 4.7 402 Embodiment 11 5.0 516 Example 12 4.9 468 Example 13 4.7 614 Embodiment 14 4.8 689 Embodiment 15 4.9 588 Example 16 4.9 497 Comparative Example 1 4.9 231 Comparative Example 2 5.0 189 Comparative Example 3 5.4 253 Comparative Example 4 4.9 194 Pure phase (without coating) 4.8 28

[0180] III. Analysis of test results of various embodiments and comparative examples

[0181] According to Table 1 and Figure 6 , Examples 1 to 16 can all obtain small-particle lithium-rich ferrite materials with relatively good capacity, among which Example 1 has the highest capacity; from the comparison of Examples 1-4, Examples 5-8, and Examples 9-12, it can be seen that the capacity decreases when the carbon layer content is too high or too low; from the comparison of Example 1 and Examples 13-16, it can be seen that if the content of the second coating layer is too high or too low, the capacity will also be reduced. At the same time, according to Examples 1 and Examples 13-14, the unreasonable ratio of polyethylene oxide and lithium salt in the second coating layer will also lead to a decrease in capacity; from the comparison of Examples 1, 5, and 9, it can be seen that although the use of conventional carbon sources can increase the battery capacity, the effect of high-temperature coal tar pitch on increasing the capacity is more obvious.

[0182] According to Table 1 and Figure 6By comparing Example 1 with Comparative Examples 1 and 2, it can be seen that the capacity improvement of the carbon layer and the second coating layer containing polyethylene oxide and lithium salt is much higher than that of the carbon layer alone or the second coating layer containing polyethylene oxide and lithium salt alone; by comparing Example 1 with Comparative Example 3, the selection of iron oxide as the iron source is conducive to obtaining a small-particle lithium ferrite-rich lithium ferrate material. If iron hydroxide is selected, the particle size of the lithium ferrite-rich lithium ferrate increases and the capacity is significantly reduced; commonly used air-stable solid electrolytes include lithium aluminum titanium phosphate (LATP), lithium aluminum germanium phosphate (LAGP), lithium lanthanum zirconium oxide (LLZO), etc. The comparison between Example 1 and Comparative Example 4 shows that the application of unconventional solid electrolytes can achieve a significant increase in battery capacity.

[0183] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A lithium iron oxide-rich material, characterized in that: The core-shell structure particle comprises a core, a first coating layer coated outside the core, and a second coating layer coated outside the first coating layer; Wherein, the core is Li5FeO4, the first coating layer is a carbon layer, and the second coating layer is a mixed layer including polyethylene oxide and lithium salt; Wherein, the mass ratio of the first coating layer to the core is (2:100) to (10:100), the mass ratio of the second coating layer to the core is (3:100) to (13:100); the mass ratio of the polyethylene oxide to the core is (0.5:100) to (5:100), and the mass ratio of the lithium salt to the core is (2:100) to (8:100); The D90 particle size of the inner core is 3-5.5 μm.

2. The lithium-rich lithium iron oxide material according to claim 1, characterized in that: The mass ratio of the polyethylene oxide to the core is (0.5:100) to (2:100), and the mass ratio of the lithium salt to the core is (2:100) to (4:100); And / or, the mass ratio of the carbon layer to the core is (2:100) to (8:100); and / or, the lithium salt is selected from at least one of lithium bis(fluorosulfonyl)imide, lithium hexafluorophosphate and lithium fluoride; And / or, the molecular weight of the polyethylene oxide is 50,000 to 150,000 Da.

3. The lithium-rich lithium iron oxide material according to claim 1, characterized in that: The average thickness of the first coating layer is 5-10 nm; And / or, the average thickness of the second coating layer is 5~10nm.

4. A method for preparing the lithium-rich lithium ferrite material according to any one of claims 1 to 3, characterized in that: include: Providing a core and a coating liquid; forming a first coating layer on the surface of the core to obtain an intermediate product; Mixing the intermediate product with a coating liquid to form a second coating layer on the surface of the first coating layer to obtain the lithium-rich lithium ferrite material; Wherein, the coating solution includes a solvent, polyethylene oxide and a lithium salt.

5. The preparation method according to claim 4, characterized in that: The step of forming the first coating layer on the surface of the core includes: mixing the core with a carbon source and a grinding aid and ball milling the core, and then performing a carbonization treatment to obtain the intermediate product.

6. The preparation method according to claim 5, characterized in that: The carbon source is selected from at least one of polypropylene, glucose and high-temperature coal tar.

7. The preparation method according to claim 5, characterized in that: The temperature of the carbonization treatment is 500-700° C., and the time is 1.5-3 hours.

8. The preparation method according to claim 4, characterized in that: Before forming the first coating layer on the surface of the core to obtain the intermediate product, the core is also prepared. The preparation method includes: The mixture of the iron source and the lithium source is placed in an inert atmosphere and calcined at 500-700° C. for 24-48 hours.

9. The preparation method according to claim 8, characterized in that: The iron source is Fe2O3.

10. The preparation method according to claim 8, characterized in that: The D90 particle size of the iron source is less than or equal to 400 nm.

11. The preparation method according to claim 8, characterized in that: The lithium source is selected from at least one of lithium oxide, lithium hydroxide and lithium carbonate.

12. The preparation method according to claim 8, characterized in that: The lithium source is a mixture of lithium oxide and lithium hydroxide.

13. The preparation method according to claim 8, characterized in that: The lithium source is a mixture of lithium oxide and lithium hydroxide in a molar ratio of (1.5:1) to (2.5:1).

14. The preparation method according to claim 8, characterized in that: The molar ratio of Fe to Li in the mixture is (1:5.0) to (1:5.2).

15. The preparation method according to claim 4, characterized in that: The intermediate product is mixed with the coating liquid, the solvent is removed, and the mixture is ground and sieved to form a second coating layer on the surface of the first coating layer, thereby obtaining the lithium-rich lithium ferrite material.

16. A positive electrode plate, characterized in that: It comprises a current collector and an active material layer arranged on at least one side of the current collector, wherein the active material layer comprises the lithium-rich lithium ferrite material as described in any one of claims 1 to 3 or the lithium-rich lithium ferrite material prepared by the preparation method as described in any one of claims 4 to 15.

17. The positive electrode sheet according to claim 16, characterized in that: The mass fraction of the lithium-rich lithium ferrite material in the active material layer is (2-8) wt%.

18. A secondary battery, characterized in that: Comprising the positive electrode sheet as described in claim 16 or 17.

19. An electrical device, characterized in that: Comprising the secondary battery as claimed in claim 18.

Citation Information

Patent Citations

  • Carbon-coated lithium-rich oxide composite material and preparation method thereof

    CN111725576A

  • Positive lithium supplement additive, preparation method thereof, positive plate and secondary battery

    CN116014220A

  • Lithium supplement additive and preparation method and application thereof

    CN116072991A

  • Positive electrode lithium supplementing material, preparation method thereof and lithium ion battery

    CN117497721A

  • Positive lithium supplementing material, preparation method thereof, positive plate and secondary battery

    CN117747819A